Model of environmental perceptions on value of recyclable products and its effects on consumers behaviour - Koval, Viktor; Suhartanto, Dwi; Kryshtal, Halyna; Amalia, Fatya Alty; Udovychenko, Viktoriia; Arsawan, I Wayan Edi (Journal of Business Economics and Management, 2024)
The massive consumption of conventional recyclable products causes environmental pollution, so it is very important to raise public awareness about the use of green plastics. This study assessed a comprehensive understanding of the behavioural intention model of green plastic products from the perspective of the new generation. This study uses data collected from 551 new-generation customers of environmentally friendly recyclable plastic products in Indonesia. Data analysis employing partial least squares reveals that the behavioural intention model, including perceived quality, perceived value, trust, and satisfaction as determinants, is a fit across these generation cohorts. Further, this study claims that customer satisfaction is the main driver of behavioural intention, while trust is the main determinant of satisfaction with green plastic products for both generations. Finally, this study shows that millennial satisfaction is driven by perceived value, whereas new-generation satisfaction is determined by perceived quality. The study only considered behavioural intention, including quality, value, trust, and satisfaction as the drivers, meanwhile, other potential factors could influence the intention significantly as well. These findings specifically apply to green plastic products but not to other kinds of green products. In addition, the government can devise better policies supporting green products by offering tax incentives for recyclable products.